Recombinant Ganoderma lucidum Immunomodulatory Protein Improves the Treatment for Chemotherapy-Induced Neutropenia - Lei, Xinhua; Zhi, Chenyang; Huang, Wei; Sun, Xilin; Gao, Weiyang; Yin, Xue; Zhang, Xin; Liang, Chongyang; Zhang, Haoran; Sun, Fei (Frontiers in Pharmacology, 2020)
Ganoderma lucidum, also known as LINGZHI, has a long tradition of use in folk medicine of the Far East, which is documented in the oldest Chinese pharmacopoeia, declaring it a superior medicine. LINGZHI-8 (LZ-8) is an immunoregulatory fungal protein isolated from the fruiting body of Ganoderma lucidum. Neutropenia is a condition with an abnormally low levels of neutrophils in the blood, which is caused by numerous medical conditions or medications, such as chemotherapy. The current study demonstrated that recombinant LZ-8 (rLZ-8) from Pichia promoted the differentiation of bone marrow hematopoietic stem cells (HSCs) into granulocytes in a neutropenia mouse model induced by cyclophosphamide. Also, it regulated the CXCR4-SDF1 axis to promote the mobilization of HSCs and the release of neutrophils from the bone marrow to peripheral blood. Binding of rLZ-8 to the colony stimulating factor 1 receptor (CSF1R) promotes the differentiation of HSCs into primitive CFU colonies. These results suggested that rLZ-8 has a potential effect in the treatment of chemotherapy-induced neutropenia.